(untitled) (Huellas, 2022)
Starting from America as a whole, the purpose is to review different regionalizations that have been practiced since the beginning of the 19th century and up to the present. By regionalization we mean a system of spatial practices, crossed by power relations. This system is articulated around four practices, namely identification, delimitation, naming and representation of space-time units, that is, regions. Likewise, regionalizations are practiced by states, companies, individuals or social groups with different purposes, goals, interests or motivations, which can be divided into three categories: hegemony, cooperation and dissent. The article will be organized around these three categories, identifying different moments in the social construction of regional entities such as Panamérica, ZICOSUR and Latin America.